Risk factors for falls in the elderly: an integrative review - Aglauvanir Soares Barbosa, Débora Brenna Costa de Almeida, Silvia Mara Rocha Bezerra, Sarah Maria de Sousa Feitoza (Revista de Enfermagem da UFPI, 2020)
DOI: https://doi.org/10.26694/2238-7234.7467-72